2019
DOI: 10.3389/fncel.2019.00158
|View full text |Cite
|
Sign up to set email alerts
|

Predisposition to Alcohol Drinking and Alcohol Consumption Alter Expression of Calcitonin Gene-Related Peptide, Neuropeptide Y, and Microglia in Bed Nucleus of Stria Terminalis in a Subnucleus-Specific Manner

Abstract: Alcohol/BNST: CGRP, NPY, Neuroinflammation intake could be in part mediated by anterior BNST subnuclei showing lower NPY expression and differential microglia activation. Alcohol intake in sP rats produced complex subnucleus-specific changes in BNST, affecting CGRP/NPY expression and microglia and leading to hypothesize that these changes might contribute to the anxiolytic effects of voluntarily consumed alcohol repeatedly observed in sP rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Early studies show that the central CGRP system is also implicated in alcohol preference and withdrawal-induced sequelae in adult rodents (Ehlers et al, 1999;Hwang et al, 1995). More recently, studies have shown that after voluntary alcohol drinking, Sardinian alcohol-preferring rats display a marked increase in CGRP expression in the extended amygdala (Rossetti et al, 2019), suggesting that CGRP is implicated in the proneness to excessive alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies show that the central CGRP system is also implicated in alcohol preference and withdrawal-induced sequelae in adult rodents (Ehlers et al, 1999;Hwang et al, 1995). More recently, studies have shown that after voluntary alcohol drinking, Sardinian alcohol-preferring rats display a marked increase in CGRP expression in the extended amygdala (Rossetti et al, 2019), suggesting that CGRP is implicated in the proneness to excessive alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive alcohol consumption increases the sensitivity of glutamate receptors and increases the concentration of glutamate in the central nervous system, leading to excitotoxicity and neuronal death [51]. Additionally, it is known that alcohol consumption can activate astrocytes through alterations in proteins expressed in microglia, implying in neuroin ammatory mechanisms [52].…”
Section: Discussionmentioning
confidence: 99%
“…The brains were then carefully removed and placed overnight in the same fixative solution on a shaker (at 4°C). The brains were subsequently washed in PBS, cryoprotected in 20% sucrose, placed in an embedding medium containing mould, frozen and 10 μm thick coronal sections cut at cryostat and processed for immunofluorescence and confocal analysis as already described (Rossetti et al, 2019). Since variability in immunoreactivity is increased by suboptimal fixation, only brains that underwent an optimal fixation procedure were cut.…”
Section: Immunofluorescence Analysismentioning
confidence: 99%
“…A major source of variability experienced in immunohistochemical analysis of the brain is the unevenness of labelling (within an identified area) along its rostrocaudal extent (following a rostrocaudal direction of cutting): the same issue was faced in rat bed nucleus of stria terminalis where it was tackled by scanning only at a few, strictly identified rostrocaudal levels of the complex (Rossetti et al, 2019). Here also, variability reduction has been pursued by analysing immunoreactivity, in each animal, in one to two sections at the same rostrocaudal level: (a) in the PPN at the level of the largest medio-lateral size of the diencephalic ventricle (the section with the largest size was identified by comparing adjacent sections collected in parallel slides) and (b) in the hypothalamus at the level of the dorsal zone of periventricular hypothalamus, in the posterior half of the posterior aspect of the lateral recess.…”
Section: Immunofluorescence Analysismentioning
confidence: 99%
See 1 more Smart Citation